Ավանդույթը իբրև սոցիալ-մշակութային երևույթ - Անի Գեղամյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматривается полисемантичность понятия “традиция”, проводится параллель с понятием “обычай”, анализируются общность и различия этих двух понятий. Автор обращается также к проблеме традиции и инновации, апеллируя к точке зрения известного культуролога Э.Маркаряна. В статье рассматривается также проблема взаимосвязи традиции и трансформирующегося общества. In this article, the author puts forward the diverse meanings of the notion “tradition”, presents the definitions existing in literature, contrast the notion of tradition with that of “custom” and singles out the similarities and differences between them. The author further examines the correlation between tradition and innovation.
Keywords: Geography; Anthropology; Recreation; Manners and customs; Social Sciences; Sociology